Partisipasi Masyarakat Dalam Pemilihan Umum Anggota Legislatif Pada Tahun 2024 Di Kelurahan Talang Ubi Tumur Kecamatan Talang Ubi Kabupaten Pali - Riziq Barggo; Ainur Ropik; Hatta Azzurri (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
Public participation in the 2024 legislative elections in Talang Ubi Timur Village, Talang Ubi District, PALI Regency. The main problems identified included low political education, inadequate election socialization, and the influence of money politics. The study aimed to determine the level of participation and the factors influencing it. Using descriptive qualitative methods, data were collected through observation, interviews, and documentation. The results showed that public participation in exercising their right to vote was quite high (84.3%), but was more routine and emotional, rather than based on consideration of the candidates’ vision and mission. Involvement in political campaigns and discussions remained low, often driven by entertainment or social events. Candidate selection tended to be based on personal closeness and direct assistance (transactional politics), rather than formal campaign promises. Relationships with public officials felt distant, while passivity toward potential fraud and passive consumption of political information (without critical verification) were also found. In conclusion, political participation in Talang Ubi Timur Village, although high quantitatively, tended to be transactional and emotional, with low levels of active engagement. This indicates the need to improve public political education and literacy.